Numerical analysis of technological and residual stresses in vitrified media - Smetannikov, Oleg Yurievich; Trufanov, Nikolay Alexandrovich (Computational Continuum Mechanics, 2008)
The general description of a thermomechanical boundary-value problem for polymeric materials in conditions of relaxation transition, including author's physical model, is presented. The numerical step-by-step algorithm is proposed to solve this problem by the application of finite element method procedure on each step. The specific features of the numerical solution to the problem, taking into accounting viscoelastic properties of the medium in glassy state, are demonstrated. Adaptation of the proposed physical model to the finite-element program ANSYS is carried out. The solution of the problem on forecasting the fields of technological and residual stresses in a vitrifying continuous short epoxy-polymer cylinder is given.